Impact of Ageing on Curative Health Care Workforce in Selected EU Countries - Erika Schulz; Flavia Coda Moscarola; Stanisława Golinowska; Marek Radvansky; Johannes Geyer (Deutsches Institut für Wirtschaftsforschung (DIW), 2013)
Population ageing combined with a shrinking potential workforce are main factors influencing future socio-economic development and the labour market. This paper has the objective to show the impact of population change on one important sector of the economy, the health care market. As the need for health care services increases with age, the population ageing is expected to have a direct influence on the demand for services and the workforce needed. The shrinking labour force and the currently high share of elderly health professionals will have an impact of the future supply of health workforce. Based on the NEUJOBS demographic scenarios tough and friendly and age- and gender specific utilization rates the changes in the health workforce needed are calculated. Changes in labour supply and employment are shown using the results of the econometric model NEMESIS. In both scenario a decline in population size and an ageing of the population is expected. In the friendly scenario the demand for health care services is expected to increase, although the population size declines. The population ageing has a higher effect on the demand as the shrinking population size. In the tough scenario the significant decline in population dominates the demand for health workforce. Due to the demographic change also a decline in labour supply is calculated, while the employment in health care is estimated to increase in both scenarios. In 2025, the estimated employment is higher than the demand for health workforce. But on the demand side the calculations show only the pure demographic effect. Due to data restrictions we could not take into account the technological medical progress, changes in health utilization behaviour or changes in health status of the population. All these factor have an influence on the future health workforce demand.
Additional information: This publication was produced as part of the NEUJOBS project, funded by the European Commission through the 7th Framework Programme under contract no. 266833 (http://www.neujobs).; info:eu-repo/grantAgreement/EC/FP7/266833
Keywords: 330; Gesundheitswesen; Gesundheitsberufe; Alternde Bevölkerung; Deutschland; Pflegeberufe; Dänemark; Italien; Polen; Slowakei; EU-Staaten